Urban sprawl and its impact on vegetation cover of Sabya Governorate in the Jizan region - Aldalaan, Atheer Abdullah; Alsubaie, Ghadah Hazza; Nahas, Faten Hamed (Journal of natural sciences, life and applied sciences, 2021)
This research seeks to study the effect of urban sprawl on vegetation cover of Sabya Governorate in the Jizan region, between (2010- 2020), Through the use of satellite visualizations using Geographic Information systems (GIs) technology and remote sensing by downloading the visuals, classifying and analyzing them with the tools available in the program that are distinguished by their ability to analyze data by studying satellite visualizations of the geographical phenomenon, and identify the changes in urban expansion and its impact on the vegetation cover of Sabya Governorate, the methodology conduct the descriptive and analytical historical approach through the use of satellite visuals through remote sensing and geographic information systems and the extraction of digital maps The study found that there is a change in the area of vegetation cover for the years (2010- 2020), as the area of vegetation cover in Sabya Governorate decreased by (29%) for the year (2020) compared to the year (2010), and that there is a significant change in the area of urbanization for the years (2010- 2020), as the urban expansion area increased by (18%) for the year (2020).
Keywords: urban sprawl; vegetation cover; Sabya governorate; Jazan